The Salience of Complex Words and Their Parts: Which Comes First? - Giraudo, Hélène; Dal Maso, Serena (Frontiers in Psychology, 2016)
This paper deals with the impact of the salience of complex words and their constituent parts on lexical access. While almost forty years of psycholinguistic studies have focused on the relevance of morphological structure for word recognition, little attention has been devoted to the relationship between the word as a whole unit and its constituent morphemes. Depending on the theoretical approach adopted, complex words have been seen either in the light of their paradigmatic environment (i.e., from a paradigmatic view), or in terms of their internal structure (i.e., from a syntagmatic view). These two competing views have strongly determined the choice of experimental factors manipulated in studies on morphological processing (mainly different lexical frequencies, word/non-word structure, and morphological family size). Moreover, work on various kinds of more or less segmentable items (from genuinely morphologically complex words like hunter to words exhibiting only a surface morphological structure like corner and irregular forms like thieves) has given rise to two competing hypotheses on the cognitive role of morphology. The first hypothesis claims that morphology organizes whole words into morphological families and series, while the second sets morphology at a pre-lexical level, with morphemes standing as access units to the mental lexicon. The present paper examines more deeply the notion of morphological salience and its implications for theories and models of morphological processing.